Discurso gerencialista como promotor da normalização das relações de poder na empresa-escola - More, Janaína Alves (2022)
The transformations of capitalism imposed changes on contemporary organizations and work, now guided by the flexibility of managerial management. From this perspective, everything is manageable, even the individual’s private life, which is mobilized to adopt a lifestyle favorable to the new spirit of capitalism – in which work becomes the center of someone´s life. This is the new condition for the survival of the contemporary company, which, through refined discursive strategies, engages its employees in favor of the profit of its business – a sophisticated exercise of power. Thus, it is through psychological domination that the contemporary organization introjects its ideology – flexibility, competitiveness, efficiency, profitability – which starts to be maintained and reproduced by the worker. These being the ideals of capitalist organizations, the private school co-opts teachers and transforms them into gears in this machinic system, which leaves aside its primary objective – teaching – and extols capital, becoming the school-company. Based on the above, this investigation focuses on understanding how the managerial discourse propagates the managerial ideology and promotes the assimilation of the manager’s power over the faculty, mobilizing them to work for the benefit of the school-company. Therefore, we seek to understand how the discursive practices of managers are used to disseminate the managerial ideology in organizations and what are the implications of this dissemination; to investigate the discursive and symbolic strategies operationalized for the maintenance of managerial power, as well as to perpetuate the asymmetries of power in school organizations and identify the typical discourses of naturalized managers and reproduced by teachers – the weakest in the power relationship. For data collection, the strategy for approaching the field was the individual in-depth interview, since it is a flexible technique that allows the researcher to approach the singularities of the interviewed professors – objects of this study. Thus, Critical Discourse Analysis, formulated by Fairclough (2016) and expanded by Chouliaraki and Fairclough (1999), presented itself as a more coherent methodology to reveal the asymmetries of power in social practices in the school context. The interpretation of the data points out that specific discourses present in the investigated context have inseparable links with the managerial ideology that crosses the teaching discourse and are perpetuated in their social practices in the school environment.